Análise da inserção urbana de um assentamento precário localizado em área de manancial do sistema Billings/Guarapiranga: estudo de caso do Jardim Maria Rita - Canibá, Weslley Gonçalves (Universidade Federal de São Carlos, 2023)
The housing deficit is a social problem that affects many urban areas around the world, including those with water sources. In many cases, people who do not have access to adequate housing are forced to occupy informal areas near water sources, often without basic infrastructure services. Informal occupations can lead to a number of negative consequences for the environment, such as water and air pollution, deforestation and the degradation of natural ecosystems. In addition, a lack of adequate infrastructure can increase the risks of natural disasters such as floods and landslides. This study aims to analyze the quality of urban insertion of a precarious occupation established in a spring area on the banks of the Billings Dam in the city of São Paulo (SP). For the evaluation of the quality of urban insertion will be used the evaluation tool of urban insertion developed by the Institute of Transport & Development Policies in partnership with LabCidade (ITDP / LabCidade). The tool is composed of three criteria: "1 - Transport", "2 - Supply of equipment, trade and services" and "3 - Design and urban integration". Despite the conditions of access to public transport in the settlement, the research developed indicated for the criterion "1 – Transport" "acceptable" result, in criterion 2 was obtained "acceptable" result, although much of the supply of equipment, commerce and services are accessible only in neighboring neighborhoods. Regarding criterion 3, which deals with the relationship with the surroundings of the neighborhood, opening to public spaces, and design of the blocks, an "insufficient" result was obtained due to the morphology characteristics of the settlement.
Analysis of the urban insertion of a precarious settlement located in a source area of the Billings/Guarapiranga system: a case study of Jardim Maria Rita
Keywords: Assentamentos precários; Billings; Mananciais; Planejamento urbano; Políticas públicas; Plano diretor estratégico; Precarious settlements; Springs; Urban planning; Public policy; Strategic master plan; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS